Revolusi Pendidikan Seni: Seni Pertunjukan Tari dan Musik dalam Era Teknologi - Nurmalena, Nurmalena; Ernawita, Ernawita; Arnailis, Arnailis; Elizar, Elizar (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2023)
Art has been an integral component of human culture for centuries, allowing individuals to express themselves creatively through various art forms, such as dance and music. However, with the advancement of technology, art education has undergone a significant revolution. This article discusses the impact of this revolution in art education, particularly in the context of performing arts such as dance and music, and how technology has changed the way art is taught, learned, and applied. This research utilizes a descriptive qualitative approach to depict the impact of technology in art education. Data was obtained through a literature review, using sources such as journals, books, and articles from platforms like Google Scholar and Crossref. The research findings indicate that the Art Education Revolution represents a significant shift in how the performing arts of dance and music are taught, learned, and applied in the age of technology. Thoughtful integration of technology in art education allows learners to harness both traditional and technological aspects for a balanced and relevant learning experience in the modern world. Technology serves as a crucial tool in achieving these goals and supports the holistic development of learners in art education.Keywords: Art Education Revolution, Music Art, Dance Art, Technology